PROTOTIPE SISTEM DETEKSI SUHU TUBUH DAN MASKER WAJAH MENGGUNAKAN ALGORITMA LOCAL BINARY PATTERN (LBP) DAN ARDUINO NANO - Dewi, Ine Shinta; Chandra, Albert Yakobus (Jurnal Sistem Informasi dan Bisnis Cerdas, 2021)
The COVID-19 pandemic has changed the lifestyle of everyone around the world. In this change, wearing a mask is very important for every individual. Detection of people not wearing masks is a challenge as the outbreak of the Coronavirus pandemic has created large populations. In addition, detection of body temperature is also very important because one of the symptoms of COVID-19 is a high body temperature, therefore an effective method against the virus is to use a face mask and check body temperature in real time, and which will be the main focus in this prototype. how the LBP Algorithm can detect the use of masks and the Arduino Nano design with an infrared camera to measure body temperature which can be implemented in public places as a digital scanning tool. This testing prototype aims to be used in evaluating, preventing, and planning actions against COVID-19 and maintaining a distance between officers and the public in an environment where masks are mandatory and normal body temperature is required. The steps for building the model are collecting data, pre-processing, testing the model, and implementing the model. The results of this prototype test show an F1 score of 0.99 accuracy for mask detection and body temperature measurement in real time every second in degrees Celsius (C) with the highest average percentage error of 3.10% at a distance of 4 meters.  DOI : https://doi.org/10.33005/sibc.v14i2.2679